2010
DOI: 10.1136/jcp.2010.078204
|View full text |Cite
|
Sign up to set email alerts
|

Steroid therapy is associated with decreased numbers of dendritic cells and fibroblasts, and increased numbers of satellite cells, in the dystrophic skeletal muscle

Abstract: The ability of steroids to induce ultrastructural features of improvement supports the notion that they have beneficial therapeutic role. The clinical ramifications of these observations mandate further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…It is therefore likely that the anti‐inflammatory effects of corticosteroid treatment, by way of nuclear factor‐kappa B inhibition, may indirectly improve the myogenic potential of muscle stem cells. Interestingly, recent reports also suggest that steroid therapy may increase the number of muscle satellite cells within dystrophic skeletal muscle . In fact, we recently found that mTOR activity was markedly increased in the skeletal muscles of dKO mice, suggesting that its upregulation may be responsible for the rapid depletion of muscle stem cells.…”
Section: Paradigm Shiftsmentioning
confidence: 82%
“…It is therefore likely that the anti‐inflammatory effects of corticosteroid treatment, by way of nuclear factor‐kappa B inhibition, may indirectly improve the myogenic potential of muscle stem cells. Interestingly, recent reports also suggest that steroid therapy may increase the number of muscle satellite cells within dystrophic skeletal muscle . In fact, we recently found that mTOR activity was markedly increased in the skeletal muscles of dKO mice, suggesting that its upregulation may be responsible for the rapid depletion of muscle stem cells.…”
Section: Paradigm Shiftsmentioning
confidence: 82%
“…Very few DC expressing CD1a were detected: in 1 of 2 DM specimens and in 6 of 11 PM specimens. It is noteworthy that in Duchenne muscular dystrophy and in Becker muscular dystrophy, prednisone treatment resulted in reduced DC among the infiltrating cells in the dystrophic muscles 34,35 .…”
Section: Discussionmentioning
confidence: 97%
“…One example is the 2000 report of DC-expressing factor XIIIa and HLA-DR in Duchenne muscular dystrophy and limb-girdle muscular dystrophy 36 . The identification of DC in Duchenne muscular dystrophy and in Becker muscular dystrophy, by means of electron microscopy with euchromatic nuclei and multiple long dendrites, was described in 2010 34 .…”
Section: Rheumatologymentioning
confidence: 99%
“…The most effective treatments for DMD may be molecular therapies, such as therapies that induce expression of the missing dystrophin protein, increase muscle strength, or reduce muscle fibrosis [4]; most of these therapies have been used in experimental or preclinical settings, with results comparable or superior to those obtained with corticosteroids [5][6][7][8]. Corticosteroids are considered the only currently available, gold-standard treatment for DMD; they enhance muscle strength and delay disease progression, probably by inhibiting myofibril degeneration and inflammation [9,10]. The most commonly used corticosteroid is prednisone or its oxazoline derivative, deflazacort.…”
Section: Introductionmentioning
confidence: 98%